839 Longitudinal associations of shift work with depressive disorders – a systematic review and meta-analysis. (24th April 2018) - Angerer, Peter; Schmook, Renate; Li, Jian
Abstract : Background: Shift work, especially night shift work, causes disturbance of sleep, tiredness, and reduced well-being, as it interferes with the circadian chronobiological rhythm and social activities. Shift increases the risk of coronary heart disease and diabetes. Whether shift work increases the risk of depressive disorders is controversial. Whereas crossectional studies indicate an increased risk, longitudinal studies are inconclusive. Methods: Based on a systematic and extensive literature research in PubMed, Scopus, PsycINFO, PSYNDEX, and Medpilot, 5682 publications dealing with shift work and mental illness were identified until 2016 December. According to predefined selection criteria eleven high quality studies with longitudinal design reporting the relationships between shift work including night work and depressive disorders were analysed. Results: Three out of four studies, restricted in health care professions, predominantly nurses, found no significant relationships between shift work including night work and depressive disorders within period of two-year follow-up. Another five studies among employees working in sectors other than health care yielded indications for an increased risk, during period of up to ten years follow-up, however, a consistent pattern of longitudinal associations was not observed. Supplementary meta-analysis, including five studies, also indicated that shift work elevated the risk of depressive disorders by 42% (95% confidence interval 0.92–2.42). Adverse psychosocial work conditions may partly explain the associations. Conclusions: Even though the findings indicate an increased risk of depressive disorders by shift work or night work, at least outside the health care sector, the evidence is too weak to give general medical advice against shift work with respect to employees' mental health. Rather, it seems adequate to take an individualised approach with continuous support from occupational physicians and practical consideration on psychosocial stress factors that are linked to shift work. How these finding are incorporated in the German guidelines for shift work that are currently updated will be reported.